Analysis of aids cases in the Metropolitan Health Region I, state of Pará - Brazil: historical series from 2016 to 2020 (Research, Society and Development, 2022)
Objective: To analyze AIDS cases in the municipalities of the Metropolitan Health Region I (Belém, Ananindeua, Marituba, Santa Bárbara and Benevides), state of Pará - Brazil, from 2016 to 2020. Methodology: An ecological study with a survey of data from the Ministry of Health's Epidemiological Indicators Panel, to analyze associations, temporal trends and spatial distribution of AIDS cases. The analyzes were carried out with the support of the software: BioEstat 5.0 and Joinpoint Regression Program 4.9.1.0.Results: 5,182 AIDS cases were registered in the Sinan, SIM and Siscel/Siclom systems in the studied population. In the statistical analysis, it was observed that only Marituba showed a significant growth trend in the incidence of AIDS and in the mortality rate, with annual percent change (APC) equal to 4.6 and 21.5, respectively. Benevides, on the other hand, showed a downward trend in the incidence of AIDS, with a APC equal to -8.5. Most AIDS cases originated from databases other than Sinan, with a prevalence of cases in male individuals, who declared themselves brown and with a low and medium level of education. The main exposure category identified was men who have sex with men (MSM); and there were several cases with insufficient adherence and loss of follow-up to ART. Conclusion: There is an urgent need to promote effective health policies to control AIDS incidence and mortality in the municipalities studied, taking into account the epidemiological profile of key populations and improving notifications in health information systems, especially Sinan.